An Analysis of Teacher's Strategy to Overcome the Students' Difficulties in Writing Descriptive Text at the Tenth Grade of SMA N 10 Padang - Khansa Zhafirah; Hamzah Hamzah (Journal of English Language Teaching, 2022)
This study is aimed at providing explanation on the the teacher’s strategies to overcome the students’ difficulties in writing descriptive text at the tenth grade of SMA N 10 Padang. The teacher’s strategies were viewed from the components in writing the generic structures and language features of descriptive text. This study is qualitative research. The sample of the research was one of 4 English teachers who taught descriptive text at the tenth grade. The data obtained from interview and observation checklist. The findings of the study reveals that there were some strategies applied by the teacher. The strategies applied by the teacher in generic structure difficulties were observing, guiding question, while in language feature difficulties, there were sentence construction, giving opportunity to ask, metalinguistic feedback and giving the criteria. Among those strategies, guiding question was the most frequently used strategies in overcoming the difficulties in descriptive text.